"Theory of agency" w socjologii europejskiej = "Theory of agency" in european sociology - Iwińska, Katarzyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article aims to present briefly the problem of a theoretical nature, namely, the division of agency and structure in sociology. A general review of the problem of agency is presented. The author is confined to minimum details of classical meta-theory in order to present two theoretical notions of Margaret Archer and Anthony Giddens.
Keywords: Archer, Margaret (1943- ); Giddens, Anthony (1938- ); "Theory of agency"; podmiotowe sprawstwo; socjologia